2008
DOI: 10.1093/ajcn/88.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Folate and cobalamin status in relation to breastfeeding and weaning in healthy infants

Abstract: Background: Folate and cobalamin status changes markedly during infancy. Objective: We aimed to examine the influence of breastfeeding on folate and cobalamin status in healthy infants. Design: In a longitudinal study, we measured serum folate, cobalamin, holotranscobalamin, holohaptocorrin, methylmalonic acid, and homocysteine at birth and at ages 6, 12, and 24 mo (n ҃ 361, 262, 244, and 224, respectively). Breastfeeding status and nutrient intake were assessed by using questionnaires and 7-d weighed-food rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 45 publications
13
82
2
2
Order By: Relevance
“…(Hay et al, 2011). In the fifth study, serum folate concentrations reported as P5-P95 were 23 to 120 nmol/L in infants at the age of six months, 16 to 72 nmol/L in infants aged 12 months and 9 to 46 nmol/L in children at the age of two years (Hay et al, 2008). In a study in Turkish infants, mean serum folate concentration was 30 nmol/L (range 17 to 45 nmol/L) in breast-fed infants and 45 nmol/L (range 20 to 45 nmol/L) in formula-fed infants at six months (Karademir et al, 2007).…”
Section: Folatementioning
confidence: 92%
“…(Hay et al, 2011). In the fifth study, serum folate concentrations reported as P5-P95 were 23 to 120 nmol/L in infants at the age of six months, 16 to 72 nmol/L in infants aged 12 months and 9 to 46 nmol/L in children at the age of two years (Hay et al, 2008). In a study in Turkish infants, mean serum folate concentration was 30 nmol/L (range 17 to 45 nmol/L) in breast-fed infants and 45 nmol/L (range 20 to 45 nmol/L) in formula-fed infants at six months (Karademir et al, 2007).…”
Section: Folatementioning
confidence: 92%
“…The most repeated reason for risk of bias across the studies was an inadequate explanation about the drop-outs and an inadequate assessment of exposure (method to assess vitamin B 12 intakes). (31) ) or MMA (two studies (28,31) , while in one study (31) , associations were not found for MMA).…”
Section: Pregnant and Lactating Womenmentioning
confidence: 94%
“…In that study, serum n 5219 references identified from database search n 16 relevant references for further analysis n 101 references excluded from further analysis n 0 references identified from reference lists of systematic reviews n 5815 references screened for inclusion based on title and abstract n 5 relevant references for children and adolescents n 6 relevant references for pregnant and lactating women n 596 references identified from update database search n 5 relevant references for infants n 5625 references excluded n 117 potentially relevant references for inclusion based on full text Fig. 2 Selection of studies for the current systematic review (31) , 239 (212-268) in 2nd month (39) and 178 (161-198) in 3rd month (38) , with P , 0?0001 adjusted for maternal age vitamin B 12 and MMA were also measured; however, no association with them was found. In the RCT by Gewa et al (36) , the targeted population group was children and the studied relationship was I-H.…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…The case of breastfed infants independent of maternal folate status suggests that concentrations of folate positively correlate with the duration of exclusive breastfeeding. The serum folate was not higher in the formula-fed infants (19). The association between lactation and folate status was observed (20).…”
Section: Discussionmentioning
confidence: 78%